PENGARUH KOMUNIKASI, KARAKTERISTIK INDIVIDU DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT. ASTUNGKARA WAY “SOOGIROLL” BALI - Putu Meliana Sukmawati; Gde Bayu Surya Parwita; I Nyoman Resa Adhika (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2022)
Basically in every company wants to move forward and achieve its goals, to which human resources are highly invested, and to increase its performance requires training, evaluation and many other ways to improve it. This phenomenon has happened on PT. Astungkara